A evolução da estatística de saúde na Bahia, 1967-1971 The evolution of vital statistics in the State of Bahia (Brazil), 1967-1971 - José Duarte de Araújo; Antônio Carlos Silva Santos; Celso Mário de Araújo Pugliese (Universidade de São Paulo, 1971)
São discutidas as finalidades da estatística vital em face da administração e do planejamento de saúde. É descrita a evolução do processamento de dados de estatística vital na Bahia e as modificações que foram introduzidas com a Reforma Administrativa promulgada em 1966. Os resultados positivos dessas transformações são analisados em detalhe, concluindo-se que as modificações introduzidas resultaram na produção de dados estatísticos de maior valia para a administração e o planejamento da Saúde no Estado. The aims of vital statistics regarding health administration and health planning, are discussed. The evolution of vital statistics processing in State of Bahia, Brazil, and the introduced modifications beside the Administration Reform after 1966, are presented. With the positive results obtained the conclusion is that these modifications contributed substantially at statistic production of more valuable data for health administration and planning in that Brazilian area.